Assistance in Making Green Products Based on Used Waste, and Dissemination of Brand Legality - Sri Rahayu rahayu (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
The increase in cooking oil consumption is directly proportional to the increase in post-consumption used oil or also known as used cooking oil. This increase was not matched by an increase in public awareness of the negative impacts on health and the environment. Used cooking oil can damage the environment if disposed of carelessly. Used cooking oil should be managed by processing it into useful products, such as recycled soap. By processing used cooking oil into recycled soap, it not only provides benefits for one's own needs, it even has the opportunity to become a small and medium enterprise (MSMEs). Therefore this community service activity aims to provide training to the community, starting from how to make used cooking oil into recycled soap, marketing strategies and legality; trademark registration, terms, fees and others. Implementation of this activity by giving lectures on the importance of managing used cooking oil, marketing strategies, brand legality, and product manufacturing practices. Product making is guided by resource persons, followed by the community by participating in direct practice. The results of this activity are expected to increase public knowledge and awareness of the negative impacts of used cooking oil on health and the environment. Become a new business opportunity for the community that can be developed into MSMEs, understand marketing strategies, and the importance of creating a brand, and understand brand legality.